2004
DOI: 10.1002/pd.883
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of fetal anomalies: an analysis of perinatal management of 318 consecutive pregnancies in a multidisciplinary setting

Abstract: The multidisciplinary perinatal team worked well in making decisions about obstetric management. In 30% of the cases, this concerned end-of-life decisions. However, for the majority of cases, the perinatal team did not plan neonatal management before birth and thereby did not attune obstetric and neonatal management to each other. This probably reflects the different attitudes towards end-of-life decisions between obstetricians and neonatologists. However, to ensure a consistent perinatal management, a multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…It is characterised by poorly differentiated nephrons, increased stroma and, occasionally, cysts, and metaplastic tissue. Kidneys with abnormal size or structure on prenatal ultrasound, with exclusion of polycystic or hydronephrotic kidneys, are called dysplastic, and therefore include a large variety of disorders—from renal agenesis to massive cystic kidneys (Bijma et al , 2004; Winyard and Chitty, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterised by poorly differentiated nephrons, increased stroma and, occasionally, cysts, and metaplastic tissue. Kidneys with abnormal size or structure on prenatal ultrasound, with exclusion of polycystic or hydronephrotic kidneys, are called dysplastic, and therefore include a large variety of disorders—from renal agenesis to massive cystic kidneys (Bijma et al , 2004; Winyard and Chitty, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Prenatally, it presents as large hyperechogenic kidneys. The incidence is one in 40 000 live births (Bijma et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, little data on counseling patterns are available to inform policy. Prenatal health care providers from different disciplines may have different professional priorities (or loyalties), although individual moral views and priorities will certainly vary (1)(2)(3)(4)(9)(10)(11). A few studies have demonstrated differences in attitudes regarding prenatal and perinatal care between paediatric and obstetric specialists specifically (3,10,11).…”
Section: Articles Published In the Series A Different View Are Editedmentioning
confidence: 99%
“…Ultrasound screening programs detect a number of fetal abnormalities, leading to a wide range of decisions to be made by prospective parents, while at the same time ensuring optimal prenatal and postnatal treatment to the affected child …”
Section: Introductionmentioning
confidence: 99%